Agricultural research, livelihoods, and poverty: Studies of economic and social impacts in six countries - Adato, Michelle; Meinzen-Dick, Ruth S. (Johns Hopkins University Press, 2007)
The impact of agricultural research on food production and economic growth in developing countries is well established, but there is still considerable debate about the extent to which these productivity increases have been translated into reductions in poverty. This volume provides evidence from a range of case studies on the impact of different types of agricultural research and technologies on the livelihoods of poor people. The studies go beyond conventional analyses of the direct effects on poor producers, to include broader societal impacts on consumers, including the urban poor in India and China. The studies also look beyond economic measures of poverty to consider the distribution of gains by wealth or poverty status and by gender.